2010
DOI: 10.5089/9781451982589.001
|View full text |Cite
|
Sign up to set email alerts
|

Regional Financial Integration in the GCC

Abstract: This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. We investigate the extent of regional financial integration in the member countries of the Gulf Cooperation Council. The limited volume data available suggests that regional integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…The presence of RIP indicates financial market integration in the GCC economies in addition to evidence of goods and services market integration. This finding is consistent with Espinoza, et al (2010) who found strong financial integration among the GCC countries. Our results indicate that, generally, investors in these economies are risk-neutral and that transaction costs are not very high.…”
supporting
confidence: 92%
“…The presence of RIP indicates financial market integration in the GCC economies in addition to evidence of goods and services market integration. This finding is consistent with Espinoza, et al (2010) who found strong financial integration among the GCC countries. Our results indicate that, generally, investors in these economies are risk-neutral and that transaction costs are not very high.…”
supporting
confidence: 92%
“…One of the most discussed features of the banks influencing problem loans is size of the bank. Size (SIZE) taken as logarithm of assets acts as a control for whether bigger banks are more vulnerable to the NPA problem than smaller banks (Chaudhury and Sensarma 2006, Salas and Saurina 1999, Espinoza and Prasad 2010, Hu et al 2004, Ranjan and Dhal (2003)…”
Section: Sizementioning
confidence: 99%
“…To capture bank level inefficiency, operating cost ratio (OCR) which is the ratio between operating expenses and total assets is considered. It is included with an expectation that NPAs will increase with high operating costs or low cost efficiency (Chaudhury and Sensarma 2006, Salas and Saurina 1999, Espinoza and Prasad 2010.…”
Section: Cost Inefficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades oil-rich Arab countries have taken important steps to achieve economic and financial integration. Espinoza, Prasad, and Williams (2010) show a regional financial integration following such policies. The economic structure of these countries is also similar, exhibiting convergence on many macroeconomic indicators, and they are likely to face common shocks.…”
Section: Introductionmentioning
confidence: 98%